THE EVALUATION OF SUITABILITY BETWEEN PLANNING AND REALIZATION OF THE DRUG’S SUPPLY IN INPATIENT PRIMARY HEALTH CARE SERVICES IN SLEMAN DISTRICT IN 2008-2010 - Arinda Silvania; Lukman Hakim; Satibi Satibi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The aim of this study were to know the profile and evaluate the aspects of planning, demand and acceptance of drugs and to know the level of suitability between planning and realization of the drugs acceptance in inpatient primary health care services in District of Sleman on 2008-2010. Descriptive analytical approach with retrospective and concurrent data collection was used as design of this study. Research subjects were primary health care services in District of Sleman that met inclusion criteria. Primary data were collected using interviews and secondary data were collected from documents relating to the planning process, demand, and drugs acceptance. Analysis of qualitative data was presented in the textual form. Quantitative data was summarized and calculated the value of each indicator by Depkes (2006) from year to year then compared with the existing literature. Based on the calculation of drug management indicators, there was none of indicator drugs in all primary health care services during 2008-2010 with 100% accuracy of planning, most of the drug planning did not suitable with the actual acceptance in every month; in the average, level of drug availability in primary health care services of this study was happen in safe category (12-18 months); the highest average percentage of suitability with DOEN in all primary health care services was happen in 2009 (90.7%); average percentage of suitability between drug availability with patterns of disease that closest to the ideal value for all of primary health care services was happen in 2009 (106.5%), and still quite a lot of drugs were defective/expired on the primary health care services with a total loss due to defective drugs/expired at three primary health care services of the research Rp 39,086,514.6 within three years.Keywords : Drug planning, drug availability, primary health service, Sleman